THE EFFECT OF WORK ENVIRONMENT AND COMPENSATION TOWARD EMPLOYEE PERFORMANCE AT THE OFFICE OF STATE ASSETS AND AUCTION SERVICE MANADO - Tulenan, Samuel (FEB Universitas Sam Ratulangi Manado, 2015)
Abstract: It is now required for organizations to have qualified human resources in order to achieve their goals. Employees do not only determine what the organization will be but also how it will grow to be a better entity. It is better for organization to have good and qualified employees. The purpose of this research is to find the effect of Work Environment and Compensation toward Employee Performance at State Asset and Auction Service Office Manado. This research is a causal research using quantitative approach. The data was taken using questionnaire to 36 respondents which are the employee of State Asset and Auction Service Office Manado by using saturated sampling method. Multiple regression analysis method is applied in this research. Research result shows that Work Environment and Compensation have significant positive effect on Employee Performance simultaneously. Also, Work Environment has significant positive effect on Employee Performance, while Compensation has positive influence but not significant on Employee Performance partially. As the recommendation, it is better for the company to keep a good quality of their working environment and maintain fair compensation system for their employees. Keywords: work environment, compensation, employee performance.